Bridging the gap between academic and industrial hydrocracking: on catalyst and operating conditions' effects. Issue 15 (7th July 2020) - Mendes, Pedro S. F.; Silva, João M.; Ribeiro, M. Filipa; Daudin, Antoine; Bouchy, Christophe
Abstract : This work aims at bridging the knowledge gap between the well-studied Pt/zeolite catalysts and the industrially-employed NiMoS/(Al2 O3 + zeolite) ones. Abstract : This work aims at bridging the knowledge gap between the well-studied Pt/zeolite catalysts and the industrially-employed NiMoS/(Al2 O3 + zeolite) ones. To do so, catalyst series based on HUSY zeolite were evaluated in the hydroconversion of n -hexadecane under similar operating conditions, but the industrially-relevant H2 S and NH3 contaminants were added when evaluating the latter. The intrinsic performance of Pt/HUSY and NiMoS/(Al2 O3 + HUSY) catalysts was noticeably similar, when well-balanced, with the catalytic activity being however much lower in the latter (temperature gap of 125 K). Ammonia inhibition of more than 99% of the protonic sites was revealed to be the origin of such low activity. On the other hand, the metal–acid balance was only reached at sufficiently low reaction temperatures ( ca. 593 K), i.e. when the NH3 inhibiting effect increased the metal to acid site ratio in NiMoS/(Al2 O3 + HUSY) to values five orders of magnitude larger than those in the Pt/HUSY one. In addition to the understanding achieved on the role of metal–acid balance in industrial-like catalysts and its key controlling parameters, these findings also point to the need to develop better hydrogenating functions to improve the efficiency, and consequently the sustainability of liquid fuel production.